Evil: theodicy or resistance? - Felderhof, M. C. (Scottish journal of theology, 2004)
The thinker who approaches the problem of evil theoretically will conceive of the issue differently from one who approaches it practically. He will also differ on what would constitute a satisfactory ‘solution’. One looks for a logical coherence in theism, the other for consolation and the elimination of evil. The theoretical approach, it is argued, actually subverts the thinker morally and religiously. In the face of intractable evil, a theological suggestion that evil is a dark mystery is also rejected in favour of a more practical and constructive approach. It requires an active resistance to evil and then finds consolation in the consequent unity with the Holy Will that opposes all evil.The philosophers have only interpreted the world, in various ways; the point, however, is to change it. Marx's Theses on Feuerbach, no. 11